Bacillus, Pseudomonas and Serratia control Meloidogyne incognita (Rhabditida: Meloidogynidae) and promote the growth of tomato plants - Amorim, Deucleiton Jardim [UNESP]; Tsujimoto, Thiago Fornazari [UNESP]; Baldo, Fernando Berton; Leite, Luis Garrigós; Ricardo Harakava; Wilcken, Silvia Renata Siciliano [UNESP]; Gabia, Adriana Aparecida [UNESP]; Amorim, Deoclecio Jardim (Elsevier, 2024)
Plant-parasitic nematodes cause significant losses in agriculture worldwide. Among these parasites, the root-knot nematode (Meloidogyne spp.) stands out. Consequently, control methods are being developed to combat this pest. Among these methods is biological control, the main agents of which are bacteria. This study aimed to evaluate the impact of 102 bacterial isolates on the mortality of Meloidogyne incognita J2 juveniles, hypothesizing that certain isolates could effectively control the nematode and promote tomato plant growth. Five experiments were conducted to test this hypothesis. First, the effect of the 102 bacterial isolates on J2 mortality was assessed under laboratory conditions. Second, five isolates (Bacillus cereus IBCBb130, Bacillus cereus IBCBb116, Pseudomonas aeruginosa IBCBb122, Bacillus proteolyticus IBCBb136, and Serratia sp. IBCBb118), which showed >68% J2 mortality, were evaluated over 72 h. Third, these isolates were tested at seven different concentrations. Fourth, their efficacy in controlling M. incognita on tomato plants was assessed in a greenhouse setting. Fifth, their potential to promote tomato plant growth without nematode inoculation was evaluated. The results revealed that the 102 bacterial isolates caused mortality ranging from 2 to 79.57% for M. incognita J2. At a 10% dilution, five isolates (B. cereus IBCBb130, P. aeruginosa IBCBb122, B. cereus IBCBb116, B. proteolyticus IBCBb136, and Serratia sp. IBCBb118) maintained mortality rates above 68%. Among these strains, B. cereus IBCBb130 and P. aeruginosa IBCBb122 were particularly effective, with B. cereus IBCBb130 showing high mortality rates under laboratory conditions and P. aeruginosa IBCBb122 significantly reducing nematode populations in greenhouse pots. Additionally, Serratia sp. IBCBb118 demonstrated notable potential for promoting tomato plant growth. In conclusion, specific bacterial isolates exhibit strong potential for the biocontrol of M. incognita and enhancement of tomato plant growth, suggesting a viable alternative to chemical nematicides. These findings provide insight into the development of sustainable agricultural practices through targeted manipulation of the soil microbiota. Future research should explore the underlying mechanisms of these interactions and their long-term effects on crop yield and soil health.
Keywords: Biological control; Growth promotion; Meloidogyne incognita; Rhizobacteria